Managing reality managing procedures - Mitchell, Bronwyn (Institution of Civil Engineers (ICE), 2005)
Managing Reality Book 5 Managing Procedures gives step-by-step guidance on how to apply the most commonly used procedures, detailing the actions needed by all parties to comply with the contact. Anyone administering the contract will benefit from this book.